2009
DOI: 10.1371/journal.pone.0007204
|View full text |Cite
|
Sign up to set email alerts
|

Panton–Valentine Leukocidin Enhances the Severity of Community-Associated Methicillin-Resistant Staphylococcus aureus Rabbit Osteomyelitis

Abstract: BackgroundExtensive spread of community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) in the United States, and the concomitant increase in severe invasive staphylococcal infections, including osteomyelitis, in healthy children, has led to renewed interest in Panton-Valentine leukocidin (PVL). However, the pathogenetic role of PVL in staphylococcal infections remains controversial, possibly because it depends on the site of infection.Methodology/Principal FindingsWe compared the course of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
87
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 30 publications
1
87
0
2
Order By: Relevance
“…Introduction of PVL into a laboratory S. aureus strain changed the expression of other virulence factors (143), but deletion of PVL from the USA300 and USA400 clinical isolates had no influence on global gene expression (147). Experiments on mice and rabbits have usually confirmed a role for PVL in virulence (143,(145)(146)(147)(148)(149)469), whereas studies using rats and primates, and occasionally mice and rabbits, have not identified a role for PVL in infection (155,345,470,471). Given the relative insensitivity of mouse and rat PMNs to PVL, rabbits appear to be a better model for studying the effects of PVL, as their PMNs are more sensitive to PVL, more closely resembling the human situation (145).…”
Section: Cautionary Notesmentioning
confidence: 99%
“…Introduction of PVL into a laboratory S. aureus strain changed the expression of other virulence factors (143), but deletion of PVL from the USA300 and USA400 clinical isolates had no influence on global gene expression (147). Experiments on mice and rabbits have usually confirmed a role for PVL in virulence (143,(145)(146)(147)(148)(149)469), whereas studies using rats and primates, and occasionally mice and rabbits, have not identified a role for PVL in infection (155,345,470,471). Given the relative insensitivity of mouse and rat PMNs to PVL, rabbits appear to be a better model for studying the effects of PVL, as their PMNs are more sensitive to PVL, more closely resembling the human situation (145).…”
Section: Cautionary Notesmentioning
confidence: 99%
“…In rabbit bacteremia models, PVL plays a negligible role in virulence (214). In contrast, PVL may contribute to S. aureus persistence in a model of osteomyelitis (Table 1) (215). Additional studies in primates were unable to uncover a role for PVL in a pneumonia model (216).…”
Section: Luksf-pv (Pvl)mentioning
confidence: 99%
“…PVL has been linked to skin and soft tissue infections (SSTIs), necrotizing pneumonia, and bone and joint infections in humans (3,11,17). Rabbit and human leukocytes are highly sensitive to PVL-mediated leukocytosis (18), and animal studies have shown that PVL causes moresevere disease in dermonecrosis (7,27), osteomyelitis (6), and necrotizing pneumonia models (B. A. Diep, L. Chan, and P. Tattevin, presented at the 49th Interscience Conference on Antimicrobial Agents and Chemotherapy, San Francisco, CA, 2009).…”
mentioning
confidence: 99%